Plantar force comparisons between the chasse step and one step footwork during topspin forehand using statistical parametric mapping - He, Y.; Gao, Z; Fekete, G; Mitic, D.; Gu, Y. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to investigate the plantar force characteristics of the chasse step and one step footwork during table tennis topspin stroke using one-dimensional statistical parameter mapping (SPM 1d). Twelve national players volunteered to participate in the study. The plantar force of the right foot during the chasse step and one step backward phase (BP) and forward phase (FP) was recorded by instrumented insole systems. Paired sample T tests in SPSS 24.0 (SPSSs Inc, Chicago, IL, USA) were used to analyze peak pressure of each plantar region. For SPM analysis, the plantar force time series curves were marked as a 100% process. A paired-samples T-test in MATLAB was used to analyze differences in plantar force. One step produced a greater plantar force than the chasse step during 6.92-11.22% BP (P=0.039). The chasse step produced a greater plantar force than one step during 53.47-99.01% BP (P<0.001). During the FP, the chasse step showed a greater plantar force than the one step in 21.06-84.06% (P<0.001). The findings indicate that athletes can enhance plantarflexion function resulting in greater weight transfer, facilitating a greater momentum during the 21.06-84.06% of FP. In addition, reducing the load on the foot during landing by utilizing a buffering strategy. The one step showed higher peak pressure in MR, LR and LF, in BP, and the chasse step showed higher peak pressure at T and FP, indicating the potential design direction of shoes and insoles.